Recent advances in mineralocorticoid receptor antagonists for heart failure with preserved ejection fraction: focus on finerenone in the era of sodium-glucose cotransporter-2 inhibitors and glucagon-like peptide-1 receptor agonists - Wang, Tian-Yu; Zhang, Lei; Wang, Huan-Yi; Jiang, Fen-Fen (Frontiers in Pharmacology, 2025)
Heart failure with preserved ejection fraction (HFpEF) is a clinically diverse disease characterized by intricate pathophysiological pathways, for which effective treatment options remain limited. Aberrant activation of the mineralocorticoid receptor (MR) significantly contributes to the development and progression of HFpEF. Finerenone, an innovative non-steroidal mineralocorticoid receptor antagonists (MRAs), has enhanced MR selectivity, more potent anti-fibrotic and anti-inflammatory effects, and improved safety relative to conventional steroidal MRAs like spironolactone and eplerenone. Therefore, future large-scale phase III head-to-head randomized controlled trials comparing finerenone and spironolactone in the HFpEF population, with cardiovascular outcomes as the primary endpoint, will be crucial. In preclinical models, finerenone has demonstrated improvement in multiple pathophysiological parameters of HFpEF. The FIDELIO-DKD and FIGARO-DKD trials in individuals with chronic kidney disease (CKD) and type 2 diabetes mellitus (T2DM) initially demonstrated finerenone’s cardiorenal advantages, including substantial decreases in cardiovascular events and the risk of renal function decline. The FINEARTS-HF trial has expanded this data to patients with HFmrEF/HFpEF, showing a significant decrease in the incidence of total worsening HF events and mortality from cardiovascular causes. Additionally, the potential for combining finerenone with sodium-glucose cotransporter-2 inhibitors (SGLT2is) or glucagon-like peptide-1 receptor agonists (GLP-1 RAs) is gaining attention. Current trials, including REDEFINE-HF, CONFIRMATION-HF, and FINALITY-HF, are examining its effectiveness across various HF phenotypes. These research will elucidate finerenone’s function in the management of cardiometabolic disorders. This review focuses on the clinical evidence of finerenone in patients with HFpEF and concomitant CKD, along with its potential cardiorenal protective mechanisms. It aims to provide new evidence-based medical evidence and theoretical support for the clinical management of HFpEF patients.